Assessment of seven year long results of kidney biopsy - Subramanyam, Nambakam Tanuja; Vakrani, Girish P. (International Journal of Advances in Medicine, 2019)
Background: Kidney biopsy is a standard kidney biopsy tissue analysis to look at histopathological diagnosis of various kidney diseases. Previous studies have shown kidney biopsy findings mostly in pediatric population, and there is no much data on impact of various sized biopsy guns on biopsy outcome. This study includes all age group and describes impact of usage of various sized biopsy guns on biopsy outcome. Methods: A retrospective study was done on all patients who underwent kidney biopsy over 7 years. Results: Among total number of 386 patients, 55.2% were males. The commonest indication for biopsy was nephrotic syndrome. The commonest histopathological pattern was Lupus nephritis. Renal failure (RF) was found in 157 (40.7%) of which it improved in 78 (20.2%). Amongst RF patients, the commonest was IgA nephropathy. Change of needle size from 18G to 16G showed increased morbidity in the form of complications but also increased diagnostic yield. Biopsy related complications were noted in 0.8%-1.8%. Conclusions: The commonest indication for kidney biopsy was nephrotic syndrome. The commonest histopathological pattern was Lupus nephritis. Amongst RF patients, the commonest entity was IgA nephropathy. Change of needle size from thinner to thicker showed increased complications but also increased diagnostic yield too.